English Expressions Employed at Hotel Restaurants in Padang, West Sumatra, Indonesia - Sri Amelia, Sonya; ., Elfiondri (KnE Social Sciences, 2022)
English is an important language that is used worldwide. Many countries are now applying English as an important subject in education because of its position as an international language. One of the implementations of English is in tourism, especially hospitality. This paper explored the forms of English expressions used by waiters and waitresses to communicate with and serve foreign guests at a hotel restaurant, the lexical patterns of the English expressions, and the locally-colored English used by the staff. Using qualitative methods, the researchers found three English expressions, six lexical patterns of English expressions, and locally-colored themes in the English used in the hotel restaurant. Keywords: ESP, expressions, hotel restaurant